Clinical trial participation in a majority-minority, NCI-designated cancer center. Issue 28 (1st October 2022) - Bailey, Ryan; Mazo- Canola, Marcela; Ko, Heidi Chwan; Diaz Duque, Adolfo Enrique
Abstract : 86 Background: Substantial racial and ethnic disparities exist in clinical trial enrollment. Because oncology has rapidly evolved into a field rife with therapies aimed at specific biologic differences in patients, disparities in the standard of care and treatment outcomes have arisen, mainly in minorities such as Hispanics, African Americans, and Native Americans/Alaskan Natives. These disparities are due mainly to the limited understanding of tumor biology in underrepresented groups. The lack of representation in clinical trial enrollment represents both a grave oversight in oncology and an opportunity to increase treatment options for underserved groups significantly. Methods: Retrospective single-institution analysis including patients enrolled in clinical trials between 2014 and 2018. We use a Negative Binomial generalized linear model to measure the racial and ethnic disparities in Mays Cancer Center's clinical trials accruals from 2014 to 2018. Results: 4724 patients with various tumor types were enrolled in clinical trials at the mays cancer center: Using a Negative Binomial generalized linear model, we discover that clinical trial enrollment is distinct in Blacks (e coefficient = 0.22, p = 1.38e-09) and Asians (e coefficient = 0.08, p = 3.03e-20) when compared to Whites. Hispanics and Non-Hispanics do not differ in clinical trial enrollments (e coefficient = 0.77, p = 1.34e-01). Both Hispanic and Non-Hispanic Asians are greatly underrepresented; Non-Hispanic whites are overrepresented. Hispanics of all races are overrepresented in breast cancer trials as compared with Non-Hispanics (p = 6.89e-18). The inverse is true for genitourinary trials, with Non-Hispanics being overrepresented as compared to Hispanics (p = 9.78e-46). Conclusions: Hispanics were disproportionately enrolled in breast cancer trials, and Non-Hispanics were disproportionately enrolled in GU trials. Mays Cancer Center outperforms similar institutions in the enrollment of Hispanics, yet despite this, Hispanics are still somewhat underrepresented in our trials. Asians broadly are underrepresented in MCC enrollments.